The impact of glitches on young pulsar rotational evolution. Issue 3 (21st September 2021) - Lower, M E; Johnston, S; Dunn, L; Shannon, R M; Bailes, M; Dai, S; Kerr, M; Manchester, R N; Melatos, A; Oswald, L S; Parthasarathy, A; Sobey, C; et al.
ABSTRACT: We report on a timing programme of 74 young pulsars that have been observed by the Parkes 64-m radio telescope over the past decade. Using modern Bayesian timing techniques, we have measured the properties of 124 glitches in 52 of these pulsars, of which 74 are new. We demonstrate that the glitch sample is complete to fractional increases in spin frequency greater than Δ ν ^90 per cent_ g/ν ≈ 8.1 × 10^-9 . We measure values of the braking index, n, in 33 pulsars. In most of these pulsars, their rotational evolution is dominated by episodes of spin-down with n > 10, punctuated by step changes in the spin-down rate at the time of a large glitch. The step changes are such that, averaged over the glitches, the long-term n is small. We find a near one-to-one relationship between the interglitch value of n and the change in spin-down of the previous glitch divided by the interglitch time interval. We discuss the results in the context of a range of physical models.